Effect of Ethy-Gen II® Ripening Concentrate on Ripening and Sensory Properties of Mangoes (Mangifera indica L.) - Appaw, William Ofori; Oduro, Ibok; Otto, William Ellis (Pakistan Journal of Nutrition, 2009)
This study investigates whether the use of ethy-gen II® ripening concentrate (150-300ppm of ethylene) as an alternative to the traditional method of off vine ripening would support ripening of locally cultivated mangoes. Mangoes, Keith variety, were treated with the ripening concentrate for 15 h in Graff® standard reefer of 66.5 m3. Humidity was sustained by knapsack spraying of 20 litres of water inside the reefer. Fruits were stored for 6 days after treatment at ambient temperature 23±2oC, vented 30 min per day (1000 hGMT) in an air tight room to further ripe the mangoes. Total Soluble Solids (TSS) and sensory quality were studied at an interval of 2 days during the storage period. Sensory quality was assessed specifically on day 2 of storage. Results showed that ethy-gen II® treated mangoes ripened uniformly and faster than untreated mangoes Treated mangoes had higher average TSS, attaining an average brix (14.8o) at day 2 of storage. The control had brix of 12.18o at the end of the storage period. Treated mangoes had the highest percentage (100%) while the control had 34.81% at day 6 of storage. The fruity odour of the ripening concentrate had an impact on the taste of treated mangoes, however sensory evaluation revealed no significant difference (p<0.05) among treatments. Ethylene produced from ethy-gen II® supports uniform ripening of locally cultivated mangoes and increased period of ventilation during storage helps to remove the fruity odour.